The Cambridge History of Twentieth-Century Music - Cook, Nicholas; Pople, Anthony (Cambridge Cambridge University Press, 2004)
The Cambridge History of Twentieth-Century Music is an appraisal of the development of music in the twentieth century from the vantage-point of the twenty-first. This wide-ranging and eclectic book traces the progressive fragmentation of the European 'art' tradition, and its relocation as one tradition among many at the century's end. While the focus is on Western traditions, both 'art' and popular, these are situated within the context of world music, including a case study of the interaction of 'art' and traditional musics in post-colonial Africa. An international authorship brings a wide variety of approaches to music history, but the aim throughout is to set musical developments in the context of social, ideological, and technological change, and to understand reception and consumption as integral to the history of music.
Keywords: 20th Century (1901-2000); Music history; World